Pengaruh Tingkat Kesehatan Dan Fundamental Makroekonomi Terhadap Kinerja Saham Pada Perbankan Go Public Di Indonesia - Malaysia - Febrianti, Rahma; Isnurhadi, Isnurhadi; Husni Thamrin, Kemas Muhammad (Jurnal Manajerial, 2024)
Background – NPL, NIM, ROA and CAR ratios of banks in Indonesia and Malaysia show significant differences from 2016 to 2020. NPL in Indonesia is in the healthy category, ranging between 2-3%. In contrast, NPL in Malaysia is lower than Indonesia, below 2% from 2016 to 2020 and is categorized as very healthy. Apart from financial ratio factors, macroeconomic fundamentals in Indonesia and Malaysia also showdifferences. Indonesia's inflation rate in 2022 will be 5.51%, higher than Malaysia's 3.38%. Financial ratios and macroeconomic factors are closely related to financial performance, including stock returns, dividend payments and earnings per share. Aim – This purpose of this research is to determine the influence of the level of banking health and macroeconomic fundamentals on stock performance as proxied by Earning Per Share (EPS) in banks going public in Indonesia and Malaysia Design/ methodology/ approach – This research uses a quantitative approach and data processing using Eviews. Data was obtained using a purposive sampling technique using 33 Indonesian go public banks and 6 Malaysian go public banks. The data analysis technique uses panel data regression analysis. Findings – The research results show that NPL and Interest Rate (IR) have a negative and significant effect on Earning Per Share (EPS) of Go Public Banks in Indonesia. ROA and GDP have a positive and significant effect on EPS. Meanwhile, NIM and CAR have a negative and insignificant effect on EPS and inflation has a positive and insignificant effect on EPS. Meanwhile, the results of research on go public banks in Malaysia show that NPL variable has a positive and significant influence on EPS. CAR has a negative and significant effect on EPS. ROA has a positive and insignificant effect on EPS. Other variables such as NIM, GDP, Inflation and Interest rate have a negative and insignificant effect on the Earning Per Share (EPS) of go public banks in Malaysia. Conclusion – NPL, NIM, ROA, CAR, GDP, Inflation and Interest Rates influence Stock Performance as proxied by Earning Per Share (EPS) in public banking in Indonesia and Malaysia Research implication – Bank health information and fundamental macroeconomic factors can be considered important signals for investors. This knowledge can help investors make smart investment decisions, which in turn are expected to improve the company's financial performance Limitations – The limitations of this research only include variables NIM, NPL, ROA, CAR, GDP, Inflation & Interest Rate and only cover the countries of Indonesia and Malaysia.